THE ROLE OF TECHNOLOGICAL SYSTEMS IN MANAGING AND EVALUATING THE LANGUAGE TEACHING PROGRAM - Lalita Vistari; Rudi Hartono; Melfa Lamria Berliana Lumbantoruan (Universitas Wiralodra, 2025)
Innovative systems are changing modern language education from teaching and assessment to pedagogical strategies. This study explored the extent to which Learning Management Systems (LMS), Computer Assisted Language Learning (CALL) environments, and digital assessment tools impacted the organization and assessment of language programs. A qualitative research approach was utilized, and data was collected from forty participants (educators, learners, and administrators) through semi-structured interviews, anonymized surveys, and document analysis. Feedback from participants indicates that while organizational features of LMS platforms are one of the most utilized components, they are also highly effective (85%) for organizing course materials and communication. CALL tools provide interactive and personalized learning experiences (rated at 78%) but require better teacher training and technical know-how. Digital assessment tools are efficient (65%) for assessing language skills, but face challenges with evaluating nuanced language skills, such as fluency and creativity. The text emphasizes the importance of hybrid assessment methods that blend automated feedback with human input. Despite challenges like software issues, hardware access, and limited training, technology has enhanced learning and teaching. The study calls for thoughtful integration, continuous instructional design, and stronger teacher training, alongside improvements in infrastructure to support a more flexible, student-centred education system.